COMPENDIA: Harmonizing business ownership data across countries and over time - André J. van Stel (Max Planck Institute for Research into Economic Systems, 2005)
This paper presents a harmonized data set over the period 1972-2002, containing two-yearly data on the number of non-agricultural business owners and the size of the labour force for 23 OECD countries, as well as the quotient of these two variables which is called the business ownership rate of a country. The data set is called COMPENDIA, which means COMParative ENtrepreneurship Data for International Analysis. It has been constructed making use of OECD statistics as well as other relevant sources. We make an attempt to make business ownership rates comparable across countries and over time.
Keywords: O57; C82; M13; 330; cross-country data; harmonizing data; business ownership; Unternehmer; Selbstständige; Eigentümerstruktur; Datenbank; Welt